Financing higher education and labor mobility - Gabrielle Demange; Robert Fenge; Silke Uebelmesser (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper analyzes how mobility of post-graduate skilled workers and students across different countries affects the quality level of higher education and the way education is financed. We start by examining a closed economy. In the presence of imperfect credit markets the education level with pure fee-financing is lower than the optimal level. If the credit market imperfections are not too large, a mix of tax- and fee-financing is optimal. The reason for this is that with pure fee-financing too few individuals decide to study. With mobility of skilled workers, both countries have an incentive to attract foreign skilled mobile workers as tax-payers while - at least partially - free-riding on the other country's provision of education. Both countries thus increase the tuition fee above the optimum and change the level of education correspondingly. If countries maintain the financing mix foreign skilled workers are attracted by suboptimal levels of educational quality. Allowing also for mobile students may intensify the upward race of fees. The case of free-riding on the education provided by other countries may be strengthened. However, countries may anticipate this race and abstain from engaging in fee competition in the first place.
Keywords: H77; I22; 330; Higher education; labor migration; tuition fees; taxes; Bildungsfinanzierung; Hochschulfinanzierung; Hochqualifizierte Arbeitskräfte; Arbeitsmobilität; Studienfinanzierung; Steuerwettbewerb; Theorie